Analysis Of Factors Influencing Success In College-Level Advertising Design Competitions: A Quantitative Study Of College Awards - Li, Jinghe; Mastika, Lamat (UNIMAS Publisher, 2025)
This study examines patterns in award-winning graphic advertising designs to identify factors that increase students' chances of success in university competitions. The research specifically analyzes creative advertising approaches, visual representations, and submission strategies of gold-winning entries in the AD CAMPUS competition (2019–2023). Findings show that using metaphors, flat illustrations, and submitting three pieces as a cohesive series are the most effective strategies for winning. This study provides valuable insights for instructors guiding students in creative advertising competitions, offering a foundation for future design instruction and competition strategies.